Use of RWE to Inform Regulatory, Public Health Policy, and Intervention Priorities for the Developing World. Issue 1 (31st October 2021) - McNair, Douglas; Lumpkin, Murray; Kern, Steven; Hartman, Daniel
Abstract : For low‐ and middle‐income countries (LMICs) to benefit from real‐world evidence (RWE)/real‐world data (RWD) in both product registration ("regulatory") decision making and in product utilization policy ("policy") decision making, they need to overcome several challenges. They need to deploy more electronic health records systems (EHRs), adjust for confounder variables, build trust between stakeholders, and create laws and regulations for local generation of data that are assented for secondary use. The role of procurers and their use of RWE/RWD in the LMIC context likewise is in a state of ongoing development. Procurers of health products are strong players currently in the "access" chain as LMICs continue to work on strengthening governmental health technology assessment (HTA) bodies. Procurers' use of RWE is presently at an early stage and is mostly indirect, leveraging RWE results that are produced by researchers in high‐income countries (HICs), often under considerably different regulatory and policy objectives and constraints compared to LMICs' epidemiology and priorities. Pending wider deployment of EHRs and other RWE sources, stakeholders must realize that populations from HIC RWE (i) can be devised to closely resemble phenotypic patterns in LMIC populations and (ii) can be analyzed to align with LMICs' unmet needs.